Factors affecting the use of technology-based teaching methods in teaching social studies for the elementary stage: From the teachers' point of view - Asma’a Al Hjoujj, (Technium Social Sciences Journal, 2021)
The study aimed to identify the factors affecting the use of technology-based teaching methods in teaching social studies for the elementary stage from the teachers' point of view. The study relied on the questionnaire for the purposes of collecting the study data. The study sample consisted of 305 male and female teachers of the basic stage of social studies. The correlational descriptive approach was used for its suitability for the purposes of the study. The results of the study showed that the most important technology-dependent factors in teaching social studies for the basic stage from the teachers' point of view were (administrative support and training, and then technical skill, saving time, infrastructure, student numbers), and it was found that (the use of technology-based teaching methods In teaching social studies) it was of a high standard. The results of the study showed a statistically significant effect at the significance level (0.05 ?) for infrastructure, technical skills, administrative support and training, and the number of students on using technology-based teaching methods, and it was noticed that time is a non-influencing factor in that. In light of the results, the study recommends the necessity of providing administrative support and specialized training for teachers to equip them with the technical skills they need to deal with teaching methods based on technology in teaching social subject matter.